2022
DOI: 10.1002/anie.202209556
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Synthetic Glycoconjugate Vaccine Lead Against Acinetobacter baumannii 17978

Abstract: Acinetobacter baumannii is a opportunistic bacterial pathogen responsible for serious nosocomial infections that is becoming increasingly resistant against antibiotics. Capsular polysaccharides (CPS) that cover A. baumannii are a major virulence factor that play an important role in pathogenesis, are used to assign serotypes and provide the basis for vaccine development. Synthetic oligosaccharides resembling the CPS of A. baumannii 17978 were printed onto microarray slides and used to screen sera from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The totality of the NMR analysis performed on 2 and intermediates leading up to its synthesis as well as comparison to Feldman and Vinogradov's data strongly bolster the original structural assignment of the pentasaccharide. Furthermore, Seeberger and co‐workers published the synthesis of 2 a mere 5 days after we initially submitted this work for review [33] . Comparison of spectroscopic data indicated that the compounds synthesized by us and by Seeberger and co‐workers are identical.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The totality of the NMR analysis performed on 2 and intermediates leading up to its synthesis as well as comparison to Feldman and Vinogradov's data strongly bolster the original structural assignment of the pentasaccharide. Furthermore, Seeberger and co‐workers published the synthesis of 2 a mere 5 days after we initially submitted this work for review [33] . Comparison of spectroscopic data indicated that the compounds synthesized by us and by Seeberger and co‐workers are identical.…”
Section: Resultsmentioning
confidence: 76%
“…Furthermore, Seeberger and co-workers published the synthesis of 2 a mere 5 days after we initially submitted this work for review. [33] Comparison of spectroscopic data indicated that the compounds synthesized by us and by Seeberger and coworkers are identical.…”
Section: Global Deprotectionmentioning
confidence: 78%
“…Recently, the Seeberger group designed and synthesized a series of well-defined mono- and oligosaccharide units of A. baumannii ATCC17978 EPS, including four pentasaccharides, three tetrasaccharides, four trisaccharides, four disaccharides, and one monosaccharides, with an aminopentyl linker at the reducing end for microarray printing and protein conjugation . The study aimed to define the key epitopes and better understand the role of the acetyl groups in the tri-acetylated glucuronic fragment of 37c in antibody binding.…”
Section: Semi- and Fully Synthetic Carbohydrate-based Antibacterial C...mentioning
confidence: 99%
“…16 synthetic oligosaccharides (synthetic glycans) resembling A. baumannii ATCC17978 CPS, printed the synthetic glycans on microarray slides. Among them, Tetrasaccharide 20 is screened out by infection sera and a monoclonal antibody (mAb C8), which can be a potential vaccine candidate, but the practical function needs more tests to prove (Sianturi et al, 2022 ).…”
Section: Vaccinementioning
confidence: 99%